Sensation-seeking and antisocial behavior in high school high school students in the district of Puente Piedra - 2014 - Bonilla Carrasco, Fiorella (2015)
The recent research was aimed to determinate the relationship between Sensation seeking and Antisocial behavior, in a sample of high school students in Puente Piedra district. The sample was made by 260 students from two schools, whose ages range from 13 to 17 years old. The instruments used in this investigation were Zuckerman Kuhlman Personality Questionnaire (abbreviated version) (ZKPQ – 50 – CC) and A-D Seisdedos Questionnaire. The results show that students have an average Sensation seeking and antisocial behavior. Pointing out that in general, the sample tends towards this level, the same way all the dimensions are located in the average range. Also there is a significant, positive correlation between sensation seeking and antisocial behavior. This indicates that the evaluated who show greater disposition toward sensation seeking, tends to have antisocial behaviors overall.